2017
DOI: 10.1037/trm0000090
|View full text |Cite
|
Sign up to set email alerts
|

Haitian children’s resilience and vulnerability assessed with house–tree–person (HTP) drawings.

Abstract: House-Tree-Person (HTP) Test drawings by children (N ϭ 131; age range 6 -15) in Haiti were studied statistically to assess for resilience and vulnerability post-2010 Haiti earthquake. Consistent with ecological theory, item contents indicated that resilience was derived from systems of home life and familial relationships, reflections on self-other interactions, interpersonal relationships, and connectedness with the environment, and that vulnerability was derived from living without external systemic support,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 60 publications
4
38
0
Order By: Relevance
“…The international drawing studies have been clinical and interpretive in their approach, and their usefulness for clinicians needs recognition. The authors' present study, on the other hand, followed their previous study of the HTP test (Roysircar et al, 2017) with children from the same communities in Haiti, studied both adjustment and maladjustment of Haitian children, and statistically examined the HTP indices of Resilience and Vulnerability.…”
Section: International Use Of Pictorial Assessments With Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…The international drawing studies have been clinical and interpretive in their approach, and their usefulness for clinicians needs recognition. The authors' present study, on the other hand, followed their previous study of the HTP test (Roysircar et al, 2017) with children from the same communities in Haiti, studied both adjustment and maladjustment of Haitian children, and statistically examined the HTP indices of Resilience and Vulnerability.…”
Section: International Use Of Pictorial Assessments With Childrenmentioning
confidence: 99%
“…The scoring of the adapted HTP accounted for the impact of trauma on Haitian resilience and vulnerability (Roysircar et al, 2017). Two types of impact were expected, one positive and the other negative, on the basis of the literature on contextual trauma (APA, 2017;Clauss-Ehlers, 2008;Harvey, 2007;Roysircar, 2013a;Roysircar et al, 2013, Roysircar et al, 2017; the cultural strength of religion and/or spirituality in people of the African diaspora (Aten et al, 2014;O'Grady et al, 2012;Orton & O'Grady, 2016;Roysircar, 2013a;Schwartz, 2012;Thompson, 2018); ancestral trauma and resilience of Africans (Hargrow, 2013;Leary, 2005); Haitian mental health concerns (James, Noel, Favorite, & Jean, 2012;Nicolas, DeSilva, Grey, & Gonzalez-Eastep, 2006;Roysircar, 2013a;Roysircar et al, 2017); and the history of colonization, dictatorships, police brutality, and governmental neglect in Haiti (Farmer, 2004(Farmer, , 2011World Bank, 2014). Two of the authors (Roysircar and Thompson) are familiar with the Port-au-Prince surrounding areas damaged by the 2010 earthquake because of their mental health services in an NGO primary care clinic since the 2010 earthquake (Bowman & Roysircar, 2011;Roysircar, 2013a;Roysircar, Pignatiello, Lanza, & Irigoyen, 2015).…”
Section: Htp's Cultural Adaptation For Haitimentioning
confidence: 99%
See 1 more Smart Citation
“…These include governmental neglect, political persecution, unemployment and poverty, continuous contextual traumas (cf. Roysircar, Colvin, Afolayan, Thompson, & Robertson, 2017), subjugation of girls and women (cf. Horne, Maroney, Nel, Chaparro, & Manalastas, in press), disparities in power, social inequalities, and structural violence (Norsworthy & Buranajaroenkij, 2011), and war and conflict on both local and global scales.…”
Section: Adopt a Global Helping Paradigmmentioning
confidence: 99%
“…In 1979, Mikami [11] developed the S-HTP drawing test, of which characteristic is the house, tree, and person which are drawn on the same sheet of paper and assessed together in relation to each other. Currently, there are many types of research using S-HTP drawing test to assess psychological functioning such as children's resilience and vulnerability in Haitian [12] and anxiety in cancer patients [13]. However, studies on S-HTP drawing test and depression are rarely found in cancer patients.…”
Section: Introductionmentioning
confidence: 99%